C-Reactive Protein as an early predictor of COVID-19 severity: C-Reactive Protein and COVID-19 severity. - Ahnach, Maryame; Zbiri, Saad; Nejjari, Sara; fadwa, ousti; Elkettani, chafik (Journal of Medical Biochemistry, 2020)
BackgroundData for predicting severity of patients with COVID-19 infection are sparse and still under investigation. We retrospectively studied whether the admission serum C-reactive protein level (CRP) can serve as an early predictor of disease severity during COVID-19 infection in comparison with other hematologic and inflammatory markers.MethodsWe included all consecutive patients who were admitted in Cheikh Khalifa International University Hospital, Casablanca, Morocco, between February to April 2020, with a confirmed diagnosis of COVID-19 infection using SARS-CoV-2 viral nucleic acid via RT-PCR. The complete blood count and serum CRP level were routinely measured on admission. All clinical and laboratory data of patients were collected and analyzed. The classification of the disease severity was in accordance with the clinical classification of the WHO interim guidance, and the management of patients were adapted to the national management guideline. We estimated receiver operating characteristic (ROC) curves of blood routine parameters as well as their association with COVID-19 disease severity.Results145 COVID-19 patients were included in the study. The median age (range) was 50 (32–63) years, and 75 (51.7%) were men. 101 patients were classified in the non-severe group and 44 patients in the severe group. Based on disease severity, significant differences were observed in the age, gender, comorbidities, and respiratory symptom. Similarly, the biological analysis found significant differences for the neutrophil count, lymphocyte count, eosinophil count, and CRP level. However, according to ROC curves of these laboratory biomarkers, the AUC of CRP at 0.872 was significantly higher than all other parameters. Further, CRP was independently associated with severity of COVID-19 disease (OR = 1.11, 95% IC (1.01-1.22) and OR = 1.13, 95% IC (1.04-1.23)).ConclusionThis study found that the CRP level at admission represent a simple and independent factor that can be useful for early detection of severity during COVID-19 and the easy guidance of primary care.
Keywords: COVID-2019; SARS-CoV-2; C-Reactive Protein; Early predictor; Severity.